Diskursus Talfiq: Antara Mudah dan Mengambil yang Mudah-Mudah Studi Analisis Talfiq dalam Pengamalan Hukum Islam - Ahmad Mujali (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Ijtihad, imitation and talfiq are three terms that are oftenintertwined with each other. Ijtihad is the concept of ideals for all Muslimswho are able to implement it. Imitation is the reality of choice option is thecase for the People who are unable to perform ijtihad. While talfiq absurdity isan option for some people to be conscientious in performing the Shari'ah tothe fullest and people who just want to take Shari'ah easy-easy.